Landmarks in medical genetics : classic papers with commentaries - Harper, Peter S (Oxford University Press, 2004)
Univ. of Wales, UK. Offers a collection of classic papers in the field of medical genetics and includes commentaries on each. The papers fall into such groups as classic descriptions of genetic disorders, recognition of human mendelian inheritance, the origins of human cytogenetics, the early development of gene mapping, and more.
Oxford monographs on medical genetics ; No. 51
Keywords: genetika, lékařská genetika; Genetics, Medical; lékařská genetika